Frontispiece: Mild Microfluidic Approaches to Oxide Nanoparticles Synthesis. Issue 9 (17th February 2022) - Zardi, Paolo; Carofiglio, Tommaso; Maggini, Michele
Abstract : Flow chemistry is a growing technology for rapid analysis, optimization and scale‐up of reactions. In the present review, the advancements enabled by flow technologies for the preparation of oxide nanoparticles are described, with a focus on the improvement over the final product features (e. g., size, shape, and size distribution) given by flow methods with respect to conventional batch procedures. For more information, see the Review by P. Zardi, T. Carofiglio and M. Maggini on page 12.